2021
DOI: 10.1210/endocr/bqab016
|View full text |Cite
|
Sign up to set email alerts
|

Deiodinases and Cancer

Abstract: Hormones are key drivers of cancer development, and alteration of the intratumoral concentration of thyroid hormone (TH) is a common feature of many human neoplasias. Besides the systemic control of TH levels, the expression and activity of deiodinases constitute a major mechanism for the cell-autonomous, pre-receptoral control of TH action. The action of deiodinases ensures tight control of TH availability at intracellular level in a time- and tissue-specific manner, and alterations in deiodinase expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…Although D2 has been associated with different hallmarks of cancer as enhanced EMT, migration and invasion of cancer cells, and angiogenesis promotion 10 12 , 41 , the direct regulation by p53 raises the question of whether D2 can be involved in the DNA damage repair and in the genome stability.…”
Section: Discussionmentioning
confidence: 99%
“…Although D2 has been associated with different hallmarks of cancer as enhanced EMT, migration and invasion of cancer cells, and angiogenesis promotion 10 12 , 41 , the direct regulation by p53 raises the question of whether D2 can be involved in the DNA damage repair and in the genome stability.…”
Section: Discussionmentioning
confidence: 99%
“…The specific DNA binding sequences of TRs, called TR Response Elements (TREs), consist of the AGGTCA sequence as a half site, which is repeated in a direct, everted, or inverted manner in different promoters [14,15]. T4 is the main circulating hormone and is de-iodinized to T3 in target tissues by iodothyronine deiodinases DIO1 and DIO2 [16]. Another deiodinase, DIO3, further deiodinizes T3 and T4, producing the inactive forms T2 and reverse T3 (rT3), respectively.…”
Section: The Hypothalamic-pituitary-thyroid Axis and Systemic Effects...mentioning
confidence: 99%
“…In addition, it is surmised that deiodinases, which activate thyroid hormones by converting T4 into T3 (type I and II) or inactivate them by degrading (type III), might play an important role in relation to malignant diseases. This tight intracellular control of thyroid hormone availability might be dysregulated in patients with cancer and might promote tumor development and progression [32,33]. A recent study by Lin Hung-Yung et al showed that reverse T3 (rT3), which results from the conversion of T4 to T3, may be a host factor supporting cancer growth [34].…”
Section: Thyroid Hormone Statusmentioning
confidence: 99%